Synthesis and biological activity of the novel indanedione anticoagulant rodenticides containing fluorine. Issue 1 (2nd January 2017) - Chen, Feng; Liu, Liping; Bai, Zengguo; Zhang, Tianhua; Zhao, Keke
ABSTRACT: Here, 3 fluorinated intermediates of drug were synthesized: (M1), (M2), (M3). Three new anticoagulant rodenticides were designed which were based on 4-hydroxycoumarin or 1, 3-indandione, added acute toxicity groups containing fluorine. The structures of synthesized compounds were analyzed and proved by FT-IR spectroscopy and 1 H nuclear magnetic resonance ( 1 H-NMR). The compounds were also evaluated for their anticoagulant and acute biologic activity. In addition, both the acute orally toxicity and the feeding indexes of R1 and R2 were tested. The result of the experiment proved that the new synthesis of 1, 3 - indan diketone for maternal new anticoagulant rodenticide can replace the current 4 - hydroxyl coumarin as the mother of the second generation anticoagulant rodenticide and 1, 3 - indan diketone for maternal new anticoagulant rodenticides will have a good development prospect.